(untitled) (Revista de História da UEG (REVHIST), 2019)
This work aims to analyze the performance of the parliamentarians of the Legislative Assembly of Rio Grande do Sul from 1963 to 1966 that were oppositors to the Government of João Goulart and in support of the 1964 Civil-Military Coup. Through the conception that the Coup movement had a large participation of civilians, including through conservative political parties, this work aims to find elements that show the alignment of the parliamentarians of this Legislature with the concepts of the National Security Doctrine, one of the main foundations of the Coup. Their discourses were studied and analyzed in order to find the elaboration of imaginaries based on elements of the Doctrine, such as: the concepts of "total war", "internal enemy" and "ideological frontiers". Methodologically, qualitative content analysis was used. Theoretically, this study was based on the concept of imaginary, proper to Political History and considered a fundamental part of the political dispute and the legitimation of power.